Reward or Punishment? The Distribution of Life-Cycle Returns to Political Office - Jens Olav Dahlgaard; Nicolai Kristensen; Frederik Kjøller Larsen (Institute of Labor Economics (IZA), 2022)
How political office is remunerated will affect who decides to engage in politics. Even if average returns to office are positive, as unilaterally found in the literature, some office holders' returns are likely zero or negative. The timing of returns to office are crucial too, as politicians often have lucrative pensions and other types of delayed compensation. Utilizing data for all parliament candidates in Denmark from 1994 to 2015 linked to administrative data, we causally estimate the returns to office for first-time runners to parliament. We find large short-term average returns to office, corresponding to a 112% income increase. Quantile Difference-in-Difference estimates reveal considerable heterogeneity, but, strikingly, all MPs experience an economic gain during their first term. The distribution of life-cycle returns, computed as the net present value, reveals that candidates from the top quarter of the pre-office income distribution have no long-term economic gain from winning.
Keywords: J33; J4; 330; returns to office; political careers; proportional representation